High-involvement innovation through continuous improvement. (1st January 1997) - Bessant, John; Caffyn, Sarah
Continuous improvement (CI) in all aspects of the business is essential for meeting the challenge of today's turbulent environments. One increasingly popular strategy for enabling continuous improvement is through mobilising a high level of involvement of the workforce in sustained incremental problem-solving. Although the potential benefits of such high involvement innovation are considerable, implementing programmes of this kind is not easy. This paper reports on a five year research programme exploring implementation issues in CI and presents a framework model for the development of CI which draws upon extensive case study work. In particular, it identifies a series of levels of CI performance and the blocks and enablers associated with them.